National competitions prizes awarded to university librarians by LAM, 2012 edition (Confluenţe Bibliologice, 2012)
According tradition, on April 23, the Day of the Librarian in RM Awards Gala LAM takes place.  And in this year were presented the results of the national competitions "The Best Librarian of 2011 year” and „The Most Successful Works in the ﬁeld of Librarianship and Information Sciences. Diploma of Excellence "The Best Librarian of 2011 year”, the 21-st edition, was awarded to Mrs. Natalia Culicov, the chief of Bibliographic References Service.  The University Library received 6 awards for the 12 works in the competition "The Best Works in the ﬁeld of Librarianship and Information Sciences".
Keywords: awards; editorial activity